Relationships of managers' entrepreneurial perception and internationalization speed in small and medium-sized enterprises (SMEs) - Samaneh Saghebi; Abolfazl Alizadeh; Mohammad Mohammadzaheri; Tahmineh Habibisenobari (Journal of Global Entrepreneurship Research, 2019)
International entrepreneurship literature has been taken into account by researchers since the late 1980s, and they have investigated how entrepreneurs behave according to different aspects, how some of them succeed in international markets, and others fail to continue. Therefore, the present research investigated the entrepreneurial behavior as well as relationships of managers' entrepreneurial perception and the internationalization speed (IS) in small and medium-sized enterprises (SMEs). The statistical population consisted of managers in SMEs in an active Iranian industrial estate that has taken international measures. Hypotheses were tested using the structural equation test and LISREL software by analyzing 320 correct questionnaires. The obtained results indicated that the entrepreneurs' international orientation (IO) had a significant relationship with the proactivity (PR), tolerance of ambiguity (TA), knowledge intensity (KI), and risk perception (RP). They also confirmed significant relationships of the knowledge intensity, risk perception and the internationalization speed, but no relationship was found between the tolerance of ambiguity and risk perception.
Keywords: 650; Internationalization speed (IS); Entrepreneurial behavior; Risk perception (RP); Proactivity (PR); Tolerance of ambiguity (TA)